Covid-19 vaccine in prison: a not-to-be-missed opportunity to promote access to vaccination in adolescents - Mazzilli, Sara; Moazen, Babak; Stover, Heino; Plugge, Emma; Tavoschi, Lara (The BMJ, 2022)
Covid-19 vaccination campaigns for adolescents have been taking place in many countries for some months.12 The WHO Strategic Advisory Group of Experts on immunisation have called for vaccine prioritisation within countries to take into account the needs of those groups that, due to underlying social, ethnic, geographic, or biomedical factors, are at greater risk of getting infected or suffering most severe consequences from covid-19.3 Since the risk of transmission of SARS-CoV-2 is considerably higher in prisons and detention facilities than elsewhere, adolescents who are detained in juvenile institutions should be prioritised for vaccination.4 - - Detained adolescents often come from marginalised groups of society with a considerable burden of ill health rooted in poverty and discrimination, and with limited access …
Gesehen am 23.08.2022